Female athletes, nutrition and training: Effects on menstrual function - Beristain, C. (2001)
With the increased participation of women in our sport, some of the problems associated with high intensity training have begun to appear. It is common to find young female athletes (15 to 17 years old) related to menstrual dysfunction. It is tempting to relate high level training with menstrual dysfunction, still many other factors intervene to cause this. We have found a very strong relationship between, stress, eating disorders (primarily energy deficit) and menstrual disorders. This is more common in juniors who have previously had a history of menstrual dysfunction. An energy deficit caused by high intensity training, high volume training and poor eating habits usually leads to menstrual dysfunction and in some cases amenorrhea. This is not necessarily related to a low body fat percentage. In most cases they maintain a relatively normal body fat percentage and still have amenorrhea. We are working on improving the eating habits of women in triathlon. Usually female athletes tend to present severe energy deficits in their diet due to fads (they want to be really thin) and peer pressure (are you going to eat all of that?). This goes hand in hand with body perception, we have found that a large number of female athletes think everybody else is thin except themselves. The following study contemplates the eating habits, training load, body fat, energy intake, body perception and menstrual function of female triathletes in Mexico.